Mechanism behind the Beauty: The Golden Ratio Appeared in the Shape of Red Blood Cells. (7th February 2017) - Zhang, Xue-Jun; Ou-Yang, Zhong-Can
Abstract: In the past two decades, a rigorous solution for the shape of human red blood cell (RBC) with a negative spontaneous curvature c 0 has been derived with the Helfrich model under the condition that both the osmotic pressure Δ p and tensile stress λ are equal to zero. By fitting the experimentally observed shape of RBC, c 0 R 0 has been predicted to be –1.62, theminus golden ratio, where R 0 is the radius of a sphere which has the same surface area as RBC. In this paper, we verify this prediction by comparing experimental data with an analytical equation describing the relation between volume and surface area. Furthermore, it is also found ρmax /ρ B ≈ 1.6 with ρmax the maximal radius and ρ B the characteristic radius of RBC, showing an approximate beautiful golden cross section of RBC. On the basis of a complete numerical calculation, we propose a mechanism behind the beauty of the minus golden ratio that c 0 R 0 results from the balance between the minimization of the surface area and the requirement of adequate deformability of RBC to allow it passing through the spleen, the so called "physical fitness test".